Black Students in Canada’s Higher Education System: A Systematic Literature Review - Anthony Abbot Sangmen; Desmond Oklikah; George Botchey (Canadian Journal for New Scholars in Education)
Whereas studies show that minorities in Canada experience education differently given their various intersectional identities, there is no systematic literature review that synthesized the existing empirical literature on the experiences of Black students in Canada’s higher education system. Contingent on this premise, we acknowledge that people who identify as Blacks are not homogenous and examined twenty peer-reviewed studies on their educational experiences in Canada, published between the 1960s and 2024. Articles for this study were retrieved from specific academic databases (Omni, Science Direct, Scopus, Google Scholar, and Jstor). Our study identified four interrelated themes that discussed issues of general lived educational experiences, discrimination, unbalanced power relations and Black students’ subjective wellbeing. The findings also revealed the various coping mechanisms employed by Back students in higher education when faced with challenges. Consequently, policy interventions should strive to simultaneously address individual and group-level educational challenges of Black students in Canada.